Redescription of Dermestes roubali (Coleoptera, Dermestidae) from Altai - Lozinskaya, Ja.L.; Legalov, A.A. (Вестник зоологии, 1999)
A redescription of D. roubali (Kalik), a rediscovered rare species of dermestids.